Development of Daily Prayer for Children (DPC) - Tuan Muda, Tuan Zalizam; Hamzah, Hammuzamer Irwan; Saad, Mohd Nizam; Padeli, Mohd Izham; Jasril, Wahyu Hidayat (UTM, 2019)
Over the past few years, the number of mobile phone and tablet users has increased intensely. Nowadays, it has become part of people’s life. It is crystal clear that the demand for mobile apps has escalated in all areas. The phones offer not just voice call or messaging services, but several excesses of other services.This study is about the utilization of mobile phone for daily prayer. The main aim of this study is to develop a mobile daily prayer application to help children to recite them while performing prayer for daily activities. At the moment, this research focuses on developing the application on Android platform. In developing the application, all the required content have to be gathered, compiled and verified before the prototype could be developed using Adobe Flash. The prototype consists of text, image, animation and audio files of the recited prayer in Arabic as well as translated into text formatted in Bahasa Malaysia. It is hoped that the daily prayer mobile apps will help children to recite their prayer every day for all the routine activities.